Isolation and microencapsulation of fucoxanthin for drug delivery system of human lung cancer (H1299) cell line - Noviendri, Dedi (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Fucoxanthin is the major xanthophyll in brown seaweed. This compound has anticancer activities but is poorly soluble in water, sensitive to light and temperature. The challenge in utilizing this carotenoid is normally associated with extraction, purification, protection, improvement of solubility and its application as anticancer activity. In this research work, fucoxanthin from four different species of Malaysian brown seaweeds, i.e. Sargassum binderi, S. duplicatum, Turbinaria turbinata and Padina australis was extracted and purified by solvent extraction. The purification was conducted by preparative high performance liquid chromatography (HPLC) double column with methanol and acetonitrile as the mobile phase at 450 nm. Fucoxanthin-loaded microsphere (F-LM) was fabricated using w/o/w double emulsion solvent evaporation method by microencapsulation (ME) technique. The effect of four surfactants (polivinylalcohol, PVA; Tween-20; Span-20 and sodium dodecyl sulphate, SDS), homogenization speed, concentration of poly(D, L-lactic-co-glycolic acid, PLGA) and surfactant (PVA) was investigated, and all of them influenced the particle size (PS) and morphology of F-LM. The properties of F-LM such as PS, morphology, thermal behavior, glass transition temperature (Tg), functional groups and its crystallinity were characterized. Subsequently, F-LM was optimized for in vitro testing on human lung cancer (H1299) cell line based on PS and encapsulation efficiency (EE) by ME technique using RSM. The optimum conditions to fabricate F-LM formulation were achieved by using a combination of 0.5% (w/v) PVA, 6.0% (w/v) PLGA and 200 µg/ml fucoxanthin composition. The optimum of PS and EE were found to be 9.18 µm and 33.09%, respectively. The morphology of F-LM produced were spherical, discrete and smooth surface with no pore. In vitro fucoxanthin release profile of F-LM was characterized by a typical biphasic behavior with burst release (38.3%) and predominantly controlled by Higuchi model. F-LM in this research needed two months for a complete degradation. The apoptosis-inducing effect of fucoxanthin before and after ME on human lung cancer (H1299) cell line were examined by 3-(4,5-dimethyl thyzol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, light inverted microscope, fluorescence microscope, scanning electron microscope (SEM) and by luminometer. The characteristics of apoptosis by series of stereotypic morphological changes were observed on H1299 cell line such as, a decrease in cell volume, DNA fragmentation, membrane blebbing and cell packaging into apoptotic bodies. The treatment of H1299 cell line with both F-LM (ME product) and fucoxanthin had increased caspase-3/7 enzyme activities up to 3.6 and 7.8, respectively compared to their solvent control (distillated water for F-LM and ethanol for free fucoxanthin). Thus, the F-LM fabrication obtained in this research showed some desirable characteristics, potential protection from environmental effect (light and temperature), and improvement of solubility of free fucoxanthin in the water. Based on this, the study indicated that isolation and ME technique of fucoxanthin for F-LM fabrication would hold a prominent position in future drug candidate delivery system because of its biodegradability, eco friendliness and flexibility for the pharmaceutical industry.